STOP Signs: A Population-based Interrupted Time Series Analysis of Antibiotic Duration for Complicated Intraabdominal Infection Before and After the Publication of a Landmark RCT. Issue 5 (6th May 2023) - Ng-Kamstra, Joshua S.; Soo, Andrea; McBeth, Paul; Rotstein, Ori; Zuege, Danny J.; Gregson, Daniel; Doig, Christopher James; Stelfox, Henry T.; Niven, Daniel J.
Abstract : Objective: To determine if the STOP-IT randomized controlled trial changed antibiotic prescribing in patients with Complicated Intraabdominal Infection (CIAI). Summary of Background Data: CIAI is common and causes significant morbidity. In May 2015, the STOP-IT randomized controlled trial showed equivalent outcomes between four-day and clinically determined antibiotic duration. Methods: This was a population-based retrospective cohort study using interrupted time series methods. The STOP-IT publication date was the exposure. Median duration of inpatient antibiotic prescription was the outcome. All adult patients admitted to four hospitals in Calgary, Canada between July 2012 and December 2018 with CIAI who survived at least four days following source control were included. Analysis was stratified by infectious source as appendix or biliary tract (group A) versus other (group B). Results: Among 4384 included patients, clinical and demographic attributes were similar before vs after publication. In Group A, median inpatient antibiotic duration was 3 days and unchanged from the beginning to the end of the study period [adjusted median difference -0.00 days, 95% confidence interval (CI) -0.37 – 0.37 days]. In Group B, antibiotic duration was shorter at the end of the study period (7.87 vs 6.73 days; -1.14 days, CI-2.37 – 0.09 days), however there was no change in trend following publication (-0.03 days, CI –0.16 - 0.09). Conclusions: For appendiceal or biliary sources of CIAI, antibiotic duration was commensurate with the experimental arm of STOP-IT. For other sources, antibiotic duration was long and did not change in response to trial publication. Additional implementation science is needed to improve antibiotic stewardship.